2022
DOI: 10.1039/d2na00161f
|View full text |Cite
|
Sign up to set email alerts
|

Differential copper-guided architectures of amyloid β peptidomimetics modulate oxidation states and catalysis

Abstract: Orchestration of differential architectures of designer peptidomimetics that modulate metal oxidation states to perform multiple chemical transformations remains a challenge. Cu-chelation and self-assembly properties of amyloid β (Aβ14-23) peptide were...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…The concentration-dependent study indicated Cu 2+ -ligand complexation with 1 : 1 stoichiometry. 17 Compound 5 exhibited the highest binding affinity (K d = 0.55 mM) for Cu 2+ , which agrees with our design strategy. MALDI mass analysis of 5 and Cu 2+ showed a predominant m/z peak at 578.07 corresponding to [M + Cu 2+ ], and minor peaks at 654.63 and 716.16 corresponding to [M + 2Cu 2+ ] and [M + 3Cu 2+ ], respectively (Fig.…”
supporting
confidence: 85%
“…The concentration-dependent study indicated Cu 2+ -ligand complexation with 1 : 1 stoichiometry. 17 Compound 5 exhibited the highest binding affinity (K d = 0.55 mM) for Cu 2+ , which agrees with our design strategy. MALDI mass analysis of 5 and Cu 2+ showed a predominant m/z peak at 578.07 corresponding to [M + Cu 2+ ], and minor peaks at 654.63 and 716.16 corresponding to [M + 2Cu 2+ ] and [M + 3Cu 2+ ], respectively (Fig.…”
supporting
confidence: 85%
“…The incorporation of a rigid, proteolytically stable, and biocompatible kd unit imparts hydrogen bonding interactions while the pyrene moiety provides required π-π stacking and hydrophobic interactions. [8][9][10]42,[49][50][51] The presence of a kd unit in Aβ14-23 at specified positions helps overcome limitations faced by linear peptides and other large cyclic peptide-based molecules. 51 The 16 KLVFF 20 segment derived from Aβ42 is well-known for its ability to recognize Aβ42 aggregation.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of all peptidomimetics was performed using established solid phase peptide synthesis (SPPS) procedures with Fmoc-rink amide resin as the solid support. 42 Amino acids and unnatural CDP-amino acid (kd) were coupled using HBTU/ HOBt as the activating reagent and DIPEA as the base in DMF. Fmoc deprotection was achieved using 20% piperidine in DMF (Scheme S1 ‡).…”
Section: Synthetic Procedures For Peptidomimetic Amphiphilesmentioning
confidence: 99%
See 1 more Smart Citation
“…We developed a peptidomimetic ( 46) by incorporating CDP-based unnatural amino acid, cyclo(L-Lys-L-Asp) (kd), at the middle (M), N-, and C-termini of the amyloid β peptide fragment (Aβ14−23). 74 The kd unit with a rigid core structure, multiple hydrogen bonding, and metal coordinating sites (amide linkages) was introduced for its metal interaction ability, while the fluorophore pyrene (Py) at the N-terminal is useful for tracking the process of the metal binding-induced assembly of 46 due to its distinctive spectral characteristics. The addition of Cu II modulated the fibrillar assembly of 46 into 2D sheet architectures in two distinctive ways, namely, one-off addition and serial addition.…”
Section: Chemistry Of Materialsmentioning
confidence: 99%